THE USE OF MODERN TECHNOLOGIES IN TEACHING ENGLISH - Джваридзе, Д.Г. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
Relevance: In recent years, the issue of using modern technologies in the educational process has been increasingly raised. These are not only new technical means, but also new forms, methods and approaches of teaching. The main goal of using modern technologies in teaching a foreign language is to show how technologies can be effectively used to improve the quality of teaching students a foreign language, the formation and development of their communicative skills. Goal: to use modern technologies in teaching English in order to diversify the learning process and make it as interesting and entertaining as possible, involve students in the learning process.
Keywords: modern technologies; communicative skills; icebreakers; social networks